Kebijakan Pemerintah Kabupaten Maluku Tenggara Dalam Pembinaan Prestasi Atlet - Rahanra, Frederika; Sarkol, Tarsisius (Lembaga Penelitian & Pengabdian Masyarakat (LPPM) STIA Said Perintah, 2022)
The sports problem seen in Southeast Maluku Regency is that government policies have nottouched the substance of sports development. This writing focuses on coaching athlete achievement. This study aims to evaluate government policies in fostering athlete achievement in Southeast Maluku district. The population in this study were the administrators of the Southeast Maluku Regency KONI and the Southeast Maluku Regency Sports Management Athletic Branch. This research will be analyzed descriptively qualitatively. The results of the study suggest that the Southeast Maluku Regency government and the local KONI Management, as well as the Sports Branch Management are more consistent in coaching athletes and coaches to achieve achievements.